Modern information processing from theory to applications - International Conference on Information Processing and Management of Uncertainty in Knowledge-Based Systems (2004 : Perugia, Italy); Bouchon-Meunier, B. (Bernadette), 1948-; Coletti, Giulianella; Yager, Ronald R., 1941- (Amsterdam ; London : Elsevier, 2006)
The volume "Modern Information Processing: From Theory to Applications," edited by Bernadette Bouchon-Meunier, Giulianella Coletti and Ronald Yager, is a collection of carefully selected papers drawn from the program of IPMU'04, which was held in Perugia, Italy. The book represents the cultural policy of IPMU conference which is not focused on narrow range of methodologies, but on the contrary welcomes all the theories for the management of uncertainty and aggregation of information in intelligent systems, providing a medium for the exchange of ideas between theoreticians and practitioners in these and related areas. The book is composed by 7 sections: UNCERTAINTY PREFERENCES CLASSIFICATION AND DATA MINING AGGREGATION AND MULTI-CRITERIA DECISION MAKING KNOWLEDGE REPRESENTATION The book contributes to enhancement of our ability to deal effectively with uncertainty in all of its manifestations. The book can help to build brigs among theories and methods methods for the management of uncertainty. The book addresses issues which have a position of centrality in our information-centric world. The book presents interesting results devoted to representing knowledge: the goal is to capture the subtlety of human knowledge (richness) and to allow computer manipulation (formalization). The book contributes to the goal: an efficient use of the information for a good decision strategy. APPLIED DOMAINS The book contributes to enhancement of our ability to deal effectively with uncertainty in all of its manifestations. The book can help to build brigs among theories and methods methods for the management of uncertainty. The book addresses issues which have a position of centrality in our information-centric world. The book presents interesting results devoted to representing knowledge: the goal is to capture the subtlety of human knowledge (richness) and to allow computer manipulation (formalization). The book contributes to the goal: an efficient use of the information for a good decision strategy.
Entropies, characterizations, applications and some history / Jβanos Aczβel -- Belief function theory on the continuous space with an application to model based classification / B. Ristic and Ph. Smets -- Independence in conditional possibility theory / G. Coletti and B. Vantaggi -- Joint treatment of imprecision and randomness in uncertainty propagation / C. Baudrit, D. Dubois, D. Guyonnet and H. Fargier -- Consistency of probabilistic transformations of belief functions / M. Daniel -- Randomization and uncertain inference / Henry E. Kyburg, Jr. and Choh Man Teng -- An empirical complexity study for a 2CPA solver / M. Baioletti, A. Capotorti and S. Tulipani -- Consistency in preference modelling / Josβe Luis Garcβia-Lapresta and Javier Montero -- Transitive decomposition of min-transitive fuzzy relations / S. Dβiaz, B. De Baets and S. Montes -- Decision making with fuzzy ternary relations / S. Ovchinnikov -- New consistency properties for preference relations / F. Chiclana, E. Herrera-Viedma and F. Herrera -- Management of uncertainty orderings through ASP / Andrea Capotorti and Andrea Formisano -- Automating the quality assurance of an on-line knowledge-based classifier by fusing multiple off-line classifiers / Piero P. Bonissone -- Qualitative classification with possibilistic decision trees / Nahla Ben Amor, Salem Benferhat and Zied Elouedi -- Discovery of abstract knowledge from non-atomic attribute values in fuzzy relational databases / Rafal A. Angryk and Frederick E. Petry -- Kernel-based outlier preserving clustering with representativity coefficients / M.-J. Lesot -- Fuzzy C-medoids clustering models for time-varying data / R. Coppi, P. D'Urso and P. Giordani -- Improving the K2 algorithm using association rule parameters / Evelina Lamma, Fabrizio Riguzzi and Sergio Storari -- OWA aggregation on an interval argument / Ronald R. Yager -- On bi-capacity-based concordance rules in multicriteria decision making / A. Rolland -- Information evaluation in fusion : formalization of informal recommendations / Laurence Cholvy -- Application of uncertainty-based methods to fuse language identification expert decisions / J. Gutiβerrez, J.-L. Rouas and R. Andrβe-Obrecht -- Intelligent multiattribute decision support model for medical triage / F. Burstein, Jocelyn San Pedro, Leonid Churilov and Jeff Wassertheil -- Interval-based multicriteria decision making / Martine Ceberio and Franπcois Modave -- A linguistic hierarchical evaluation model for engineering systems / L. Martβinez, L.G. Pβerez, J. Liu, J.B. Yang and F. Herrera -- Non monotonic aggregates applying to fuzzy sets in flexible querying / Patrick Bosc and Ludovic Liβetard -- Fuzzy spatial data modeling : an extended bitmap approach / Jθorg Verstraete, Guy De Trβe and Axel Hallez -- Introducing [lambda]-specialization into the fuzzy EER model / Guoqing Chen, Ling Lin and Xunhua Guo -- A logical reasoning framework for modelling and merging uncertain semi-structured information / Anthony Hunter and Weiru Liu -- Machine learning and the prediction of protein structure : the state of the art / Rita Casadio, Remo Calabrese, Emidio Capriotti, Mario Compiani, Piero Fariselli, Paola Marani, Ludovica Montanucci, Pier Luigi Martelli, Ivan Rossi and Gianluca Tasco -- Efficient and robust global amino acid sequence alignment with uncertain evolutionary distance / Matthias C.M. Troffaes -- Classifying biomedical spectra using stochastic feature selection and parallelized multi-layer perceptrons / N.J. Pizzi, R.L. Somorjai and W. Pedrycz -- On the sensitivity of probabilistic networks to reliability characteristics / Linda C. van der Gaag and Silja Renooij -- Dominance of recognition of words presented on right or left eye (comparison of kanji and hiragana) / Takahiro Yamanoi, Toshimasa Yamazaki, Jean-Louis Vercher, Elie Sanchez and Michio Sugeno -- Hand posture recognition with the fuzzy glove / T. Allevard, E. Benoit and L. Foulloy -- Image retrieval by composition of regions / J.F. Omhover and M. Detyniecki -- Blind image restoration from multiple views by IMAP estimation / Monia Discepoli, Ivan Gerace and Roberta Pandolfi -- A combined feature extraction method for an electronic nose / I. Hristozov, B. Iliev and S. Eskiizmirliler.
Includes bibliographical references and index.
Keywords: Artificial intelligence -- Congresses; Information theory -- Congresses; Uncertainty (Information theory) -- Congresses; Electronic books